2004
DOI: 10.1177/016264340502000101
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Reading Instruction for Young Children with Disabilities

Abstract: This investigation examined the effectiveness of a computer program in teaching sight word recognition to four young children with developmental disabilities. The intervention program was developed through a formative evaluation process. It embedded a constant-time-delay procedure and involved sounds, video, text, and animations. Dependent measures were the percentage of correct responses during full and daily probe conditions. A multiple probe design across four word sets, replicated by four participants, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 27 publications
2
55
0
Order By: Relevance
“…During the second part, after presenting the task direction, a fixed amount of time is inserted before the prompt is given (Wolery, Ault, & Doyle, 1992). CTD procedures have been used in computer-assisted academic instruction to teach sight words (Lee & Vail, 2005), letter names and sounds in a small group setting (Campbell & Mechling, 2009), and early academic skills (Hitchcock & Noonan, 2000). The results show that CTD procedures were more effective when combined with CAI than with TDI (Hitchcock & Noonan, 2000).…”
mentioning
confidence: 99%
“…During the second part, after presenting the task direction, a fixed amount of time is inserted before the prompt is given (Wolery, Ault, & Doyle, 1992). CTD procedures have been used in computer-assisted academic instruction to teach sight words (Lee & Vail, 2005), letter names and sounds in a small group setting (Campbell & Mechling, 2009), and early academic skills (Hitchcock & Noonan, 2000). The results show that CTD procedures were more effective when combined with CAI than with TDI (Hitchcock & Noonan, 2000).…”
mentioning
confidence: 99%
“…As a result novice and veteran teachers will need to be able to participate in technology-based planning and teaching to meet their student's academic needs (Bruce The research on educators and technology has shown that technology can be used as a traditional and/or transformational tool. Traditionally, educators have used technology as a way to foster children's motivation and interest as well as increase persistence and engagement with traditional tasks by promoting a more interactive experience with instructional materials (Lee & Vail, 2005). Educators have also used technology as a transformational tool in that it has helped create a shift from teacher-directed instruction to allow students to be more active participants in their own learning and encourage project-based learning and higher order thinking (e.g., analysis and synthesis) (Angers & Machtmes, 2005;Hermans, Tondeur, van Braak, & Valcke, 2008).…”
mentioning
confidence: 99%
“…Pre-reading (Boone, Higgins, Notari, & Stump, 1996) and reading skills have been among those taught to persons with disabilities using CAI (Heimann, Nelson, Tjus, & Gillberg, 1995;Williams, Wright, Callaghan, & Coughlan, 2002) including phonological awareness (Tjus, Heimann, & Nelson, 1998) and sight word recognition (Baumgart & VanWalleghem, 1987;Brewer, White, & Brand, 1991Conners, 1990;Cuvo & Klatt, 1992;Farmer, Klein, & Bryson, 1992;Mechling, 2004;Mechling & Gast, 2003;Thorkildsen & Friedman, 1986). Recently, Coleman-Martin, Heller, Cihak, and Irvine (2005) delivered the Nonverbal Reading Approach (NRA) through computer-assisted instruction where students independently practiced decoding and word identification, while Lee and Vail (2005) taught sight words and incidental information via computer-based instruction.…”
mentioning
confidence: 99%